Colchicine may be of therapeutic benefit in prurigo pigmentosa. Issue 3 (11th April 2018) - An, Isa; Ucmak, Derya; Ibiloglu, Ibrahim; Demir, Vasfiye; Akdeniz, Sedat
Abstract: Prurigo pigmentosa (PP) is a rare inflammatory skin disease. Neutrophil‐mediated inflammation is considered to be responsible for the etiopathogenesis of PP. We consider that colchicine may be an effective agent in the treatment of PP since it exerts an antiinflammatory effect by inhibiting neutrophil chemotaxis. Further studies are required to verify whether colchicine is an effective treatment option for PP.